Биоморфологические особенности некоторых видов рода Sedum L. (Crassulaceae DC.) в зависимости от степени освещенности - Попова, Л.В. (Промышленная ботаника, 2004)
The article presents the results of studying biomorphologic peculiarities of 9 species, 2 forms and 3 varieties of the genus Sedum L. (Crassulaceae DC. family) and their vitality percentage on the sites with different illumination. It has been determined that illumination extent significantly influences such morphologic indices as plants height, leaf laminae size and vitality rate of the taxa studied. Plants reaction on illumination extent depends upon the areas of the their natural growth.